2016
DOI: 10.1016/j.euromechflu.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of surface instability of a thin layer of a magnetic fluid

Abstract: In the present work the instability of a flat horizontal thin layer of a magnetic fluid (the depth of no more than 50 µm) under the action of a uniform magnetic field is studied experimentally. It was revealed that the development of instability under the action of tilted magnetic field can lead to the formation of parallel ridges on a fluid surface; the ridges undergo a transformation into hexagonal system of conical peaks with the magnetic field increasing. The necessary conditions for the formation of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…The last assumption is confirmed by the results of Cebers (1997), who for a close problem showed that smearing of the diffusion front shifts the most dangerous mode to a longer wavelength. The result obtained rather resembles the behaviour of the free interface of a magnetic fluid, on which the Rosensweig instability (Cowley & Rosensweig 1967) develops upon instantaneous switching on of a magnetic field of various magnitudes (Bashtovoi, Krakov & Reks 1985; Dikansky, Zakinyan & Mkrtchyan 2010; Zakinyan, Mkrtchyan & Dikansky 2016). With an increase in the value of the switched-on magnetic field, the length of the most rapidly developing wavelength in this case significantly decreased.…”
Section: Numerical Results and Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The last assumption is confirmed by the results of Cebers (1997), who for a close problem showed that smearing of the diffusion front shifts the most dangerous mode to a longer wavelength. The result obtained rather resembles the behaviour of the free interface of a magnetic fluid, on which the Rosensweig instability (Cowley & Rosensweig 1967) develops upon instantaneous switching on of a magnetic field of various magnitudes (Bashtovoi, Krakov & Reks 1985; Dikansky, Zakinyan & Mkrtchyan 2010; Zakinyan, Mkrtchyan & Dikansky 2016). With an increase in the value of the switched-on magnetic field, the length of the most rapidly developing wavelength in this case significantly decreased.…”
Section: Numerical Results and Discussionmentioning
confidence: 65%
“…This result was consistent with the linear theory, in which the dispersion equation is determined by both the magnitude of the magnetic field and the surface tension and thickness of the magnetic fluid layer. However, in the problem considered in this paper, there is no surface tension, so that direct analogies with the results of Bashtovoi et al (1985), Dikansky et al (2010) and Zakinyan et al (2016) are impossible. We will return to the discussion of this analogy below.…”
Section: Influence Of the Magnetic Field On The Wavelengthmentioning
confidence: 67%
See 2 more Smart Citations
“…Manukyan et al [18] compared the wetting characteristics of an oil-based ferrofluid and a water-based magnetic paint on a hydrophobic flat surface. For the application in vibration absorbers and dampers, it is essential to investigate the mechanical properties of magnetic fluids [19][20][21]. Hayashi et al [22] studied the resistance force of a shock absorber due to magnetic functional fluids containing both micrometer-sized and nanometer-sized magnetic particles.…”
Section: Introductionmentioning
confidence: 99%